Pediatric fibromyxoid soft tissue tumor with PLAG1 fusion: A novel entity?. Issue 4 (30th December 2020) - Chung, Catherine T.; Antonescu, Cristina R.; Dickson, Brendan C.; Chami, Rose; Marrano, Paula; Fan, Rong; Shago, Mary; Hameed, Meera; Thorner, Paul S.
Abstract: The classification of undifferentiated soft tissue tumors continues to evolve with the expanded application of molecular analysis in clinical practice. We report three cases of a unique soft tissue tumor in young children (5 months to 2 years old) displaying a purely fibromyxoid histology, with positive staining for desmin and CD34. In two cases, RNA sequencing detected a YWHAZ ‐ PLAG1 gene fusion, while in the third case, a previously unreported EEF1A1 ‐ PLAG1 fusion was identified. PLAG1 fusions have been reported in several pathologic entities including pleomorphic adenoma, myoepithelial tumors of skin and soft tissue, and lipoblastoma, the latter occurring preferentially in young children. In these tumors, expression of a full length PLAG1 protein comes under the control of the constitutively active promoter of the partner gene in the fusion, and the current cases conform to that model. Overexpression of PLAG1 was confirmed by diffusely positive immunostaining for PLAG1 in all three cases. Our findings raise the possibility of a novel fibromyxoid neoplasm in childhood associated with these rare PLAG1 fusion variants. The only other report of a PLAG1‐YWHAZ fusion occurred in a pediatric tumor diagnosed as a "fibroblastic lipoblastoma." This finding raises the possibility of a relationship with our three cases, even though our cases lacked any fat component. Further studies with regard to a shared pathogenesis are required.